Urinary Tract Infection The Result of the Strength of the Pathogen, or the Weakness of the Host - Jarzembowski, Tomas; Daca, Agnieszka; Alicja Dębska-Ślizień, Maria (IntechOpen, 2018)
Urinary tract infection (UTI) is a problem so common and so significant in routine clinical practice that accurate diagnostics are especially important. In particular, complicated UTI is associated with an increased rate of therapy failures, as a result of possible biofilm formation on foreign elements and antibiotic resistance, as well as the increased possibility of an infection recurrence. These are the arguments for the constant search for novel diagnostic tools and techniques. These and many other vital topics regarding UTI complications, management, and treatment, in addition to antibiotic resistance and bacterial virulence traits allowing us to mitigate or avoid antibiotic action, are presented in this book.